RANCANG BANGUN SISTEM PENJUALAN HASIL PERTANIAN DI DESA KEBONDALEM BERBASIS WEBSITE - Masruroh, Annisa; Purwatiningtyas, Purwatiningtyas (Information Technology and Telematics, 2018)
ABSTRACT Indonesia is an agrarian country, namely a country with a majority of the population earning a living in agriculture or farming so that the sales of agricultural products in every day are very large. Therefore, a system is needed to record the sales transaction process. The sales system is a system used to manage data in a sales transaction. Good data management is needed as an important point in managing data so that it can facilitate making sales reports. As with the process of selling agricultural products in the Kebondalem Village, it must begin to be developed using the system. This system is used to simplify product and report data collection, help promote agricultural products in Kebondalem Village, make it easier to record transactions, and other activities related to the system.